Oxy-combustion studies into the co –firing of coal and biomass blends: effects on heat transfer, gas and ash compositions - Jurado Pontes, Nelia; Darabkhani, Hamidreza Gohari; Anthony, Edward J.; Oakely, E. J. (Elsevier, 2014)
Oxy-combustion with coal and biomass co-firing is a technology that could revolutionize fossil fuel power generation. It can significantly reduce harmful greenhouse gas emissions and permit the continued use of plentiful coal supplies and thereby secure our future energy needs without the severe environmental impacts expected if fossil fuels are used without CCS. The work presented here was conducted by means of experimental tests co-firing coal and biomass under oxy-firing conditions at the retrofitted 100 kWth oxy-combustor facility at Cranfield University. A parametric study was performed with respect to the effect of recycled ratio and fuel variability on gas composition (including SO3), temperatures, heat flux, burn-out and ash deposition. Furthermore, the possible compensation in heat transfer resulting from the higher heat capacity and emissivity of the gases in the oxy-combustion process as compared to the air-firing case was explored. This was done by the use of blends of coal and biomass, and we concluded that this compensation is unlikely to be significant due to the marked differences between heat fluxes reached under air and oxy-firing conditions.
12th International Conference on Greenhouse Gas Control Technologies, GHGT-12, 5-9 October 2014, Austin Texas, USA
Keywords: oxy-combustion; co-firing; coal; biomas; sheat fluxsul; fur trioxideash